Lysyl oxidase-like 1 gene polymorphisms in German patients with normal tension glaucoma, pigmentary glaucoma and exfoliation glaucoma - Wolf, Christiane; Gramer, Eugen; Müller-Myhsok, Bertram; Pasutto, Francesca; Gramer, Gwendolyn; Wissinger, Bernd; Weisschuh, Nicole (Journal of glaucoma, 2010)
Purpose - To evaluate the association between lysyl-oxidase-like 1 (LOXL1) gene polymorphisms and exfoliation glaucoma, pigmentary glaucoma and normal tension glaucoma in a case-control cohort of German patients. - Methods - Six single nucleotide polymorphisms in a 22 kb genomic region encompassing the LOXL1 gene plus an additional “outlier” single nucleotide polymorphism located approximately 1.1 Mb upstream of LOXL1 were genotyped in 128 exfoliation glaucoma patients, 88 pigmentary glaucoma patients, 273 normal tension glaucoma patients, and 280 healthy control subjects either with TaqMan allelic discrimination assays or by direct sequencing, and a genetic association study was performed. - Results - For the exfoliation glaucoma cases, case-control allelic association for 6 single nucleotide polymorphisms were highly significant. In contrast, there were no genotypic differences between pigmentary glaucoma cases, normal tension glaucoma cases and controls. However, an association between rs1048661 genotype and age at disease onset was suggested for pigmentary glaucoma patients. - Conclusions - Our study reveals that in the German population the LOXL1 genetic predisposition is limited to exfoliation glaucoma and does not include normal tension glaucoma. In addition, our study implicates that LOXL1 polymorphisms are not likely to have a major influence on the pathophysiology of pigmentary glaucoma. However, 1 nonsynonymous polymorphism may serve as a predictor of age at disease onset in pigmentary glaucoma.
Gesehen am 21.03.2024